Factors in sporting activity that influence emotional production in sport: the state of the question - Pérez-Flores, Antonio Manuel; Muñoz-Sánchez, Víctor Manuel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article explores the state of the question with regard to the elements in sporting activity that influence the production of emotions. The bibliographic selection is based on a theoretical and methodological perspective stemming from sociology and social psychology. The conclusions find that the frequency of sporting activity, the degree of interaction and the presence of competition are the main factors that influence emotional production.